Risk management and the credit risk premium - Adam, Tim René (Journal of Banking & Finance, 2002)
This paper shows how the credit risk premium affects firms' optimal hedging strategies. The model predicts that if the credit risk premium is relatively small, firms use convex hedging strategies. If the credit risk premium is relatively large, firms use concave hedging strategies. Firms in between those two extremes use strategies that feature both convex and concave elements, e.g. collar strategies. Finally, firms that are unlevered, invest little and are exposed to few non-hedgeable risks are the most likely to use linear approximations of the optimal strategy. The model replicates essentially all observed hedging strategies in the gold mining industry.